The truth about Leo Strauss : political philosophy and American democracy - Zuckert, Catherine H., 1942-; Zuckert, Michael P., 1942- (Chicago : University of Chicago Press, 2006)
Is Leo Strauss truly an intellectual forebear of neoconservatism and a powerful force in shaping Bush administration foreign policy? The Truth about Leo Strauss puts this question to rest, revealing for the first time how the popular media came to perpetuate such an oversimplified view of such a complex and wide-ranging philosopher. More important, it corrects our perception of Strauss, providing the best general introduction available to the political thought of this misunderstood figure. Catherine and Michael Zuckert--both former students of Strauss--guide readers here to a nuanced understandi.
Introduction. Mr. Strauss goes to Washington? -- ch. 1. The return of the ancients : an overview of the Straussian project -- ch. 2. Strauss, modernity, America -- ch. 3. Leo Strauss as a postmodern political thinker -- ch. 4. The man who gave away the secrets : on esotericism -- ch. 5. Leo Strauss, teacher of evil? -- ch. 6. The emergence of the Straussian study of America -- ch. 7. Straussian geography.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Strauss, Leo; Strauss, Leo; Strauss, Leo; Strauss, Leo; Political science -- United States -- Philosophy; Political science -- United States -- History; Science politique -- États-Unis -- Philosophie; Science politique -- États-Unis -- Histoire; POLITICAL SCIENCE -- History & Theory; Political science; Political science -- Philosophy; United States; Politische Philosophie; Politische Wissenschaft; USA; History